Indian economy since Independence/ edited by Uma Kapila - Kapila, Uma(ed.) (Delhi, 2007)
Revised annually, this collection of articles by India's topmost economists and experts presents a comprehensive and critical analysis of the country's economy since its independence in 1947. The book is widely accepted as the core text for graduate/post-graduate courses in Indian economy in various universities across India.
Keywords: Economic development-India-1947-2006-07